Financial management and recordkeeping - Stewart, Jeffrey Robert, 1932-; Stewart, Daisy L.; Huffman, Harry (New York : Glencoe, 1994)
A textbook for instruction in personal and business financial manage ment and recordkeeping as well as in basic accounting.
Includes index.
Keywords: Bookkeeping; Accounting; Finance, Personal; Business records; Bookkeeping -- Case studies -- Computer-assisted instruction; Accounting -- Case studies -- Computer-assisted instruction; Finance, Personal -- Case studies -- Computer-assisted instruction; Business records -- Case studies -- Computer-assisted instruction